Consumers protection of financial services in Poland. System efficiency and development perspectives - Kiciński, Andrzej (Journal of Finance and Financial Law, 2022)
The paper brings brief description of the financial services customer protection model and its evolution in Poland. The efficiency of this three-fold model, where the responsibilities are distributed to the 3 agencies: Financial Supervision Authority (KNF), Financial Ombudsman (Rzecznik Finansowy), Competition and Customer Protection Office (UOKiK) is discussed. The author discusses the project of merging the institution of the Financial Ombudsman with UOKiK and puts forward the thesis that an idea more relevant to the current needs of protecting financial services customers in Poland would be to maintain the institution of the Financial Ombudsman and transfer some competences of the President of UOKiK to the Financial Ombudsman. Finally the author presents his recommendations for the improvement of the model with a call for the strengthening of the institution of Financial Ombudsman in Poland.